Chemo-enzymatic synthesis, characterization, in vitro antioxidant capacity and oxidative stability studies of novel phosphatidylcholines with ω-3/ω-6 PUFAs and phenolic acids. (May 2020) - Marrapu, Balakrishna; Ma, Jingjing; Geng, Zhiming; Nalla, Swapna; Liu, Fang; Li, Pengpeng; Wang, Daoying; Zhang, Muhan; Xu, Weimin
Graphical abstract: Highlights: First chemo-enzymatic synthesis of new pheno-PCs containing PUFAs from natural substrates. Modified PCs were characterized by NMR, mass and FT-IR spectral analysis. Modified PCs exhibited excellent antioxidant activities. Phenolic acids were found to strongly protect PUFAs in modified PCs from oxidation. Modified PCs may be helpful to applications in food, cosmetic and pharmaceutical industries. Abstract: Novel phosphatidylcholines containing PUFAs and phenolic acids were synthesized from egg phosphatidylcholine (PC), PUFAs (docosahexaenoic, arachidonic and linoleic acids) and phenolic acids (caffeic, ferulic and p -coumaric acids) as substrates. The structures of modified PCs were confirmed by spectral analysis and were evaluated for antioxidant activities. The modified PCs containing caffeic and ferulic acids exhibited excellent antioxidant activities compared with butylated hydroxytoluene (BHT) and α-tocopherol. The synthesized compounds were also evaluated for the oxidative stabilities in liposome and organic solvent. The modified PCs showed more oxidative stable compared with standard PUFA-PCs and PUFA-PCs + BHT. Results showed that the oxidative stability decreased with increasing degree of unsaturation in organic solvent whereas in liposomes, increased with increasing degree of unsaturation due to tight packed configuration. In this study, phenolic acids were found to render protections for PUFAs in modified PCs from oxidation. Modified PCs may have great potential for applications in food, cosmetic and pharmaceutical industries.